Deregulation and sovereignty of the public in Spanish TV: infotainment as an alternative to the classical news model - Valhondo Crego, José Luis; Gonzalo, Salomé Berrocal (Estudios sobre el Mensaje Periodístico, 2020)
The economic deregulation of the last three decades has globally affected the journalistic practices of television. The most visible consequence of this change has to do with the emergence of infotainment, a hybridization of the thematic and pragmatic functions of journalism for the extensive and intensive exploitation of audiences. Through a Content Analysis assisted by qualitative data software, the possible effects of infotainment are analysed through a strategic sample of El Intermedio; a programme that adequately represents the journalistic practices and contents associated with this genre. Regarding the thematic, the results indicate that the format replicates the agenda and the framing of the Spanish reference press. In relation to the pragmatic function, the space provides a plethora of rhetorical mechanisms that suggest a more pronounced engagement with the publics.